TRASPORTASI LAUT POK-POK: Sejarah Sosial Ekonomi Pelaut Boiyauw di Kepulauan Banda - Anwar, Ahdi; Amsi, Najira; Renyaan, Kasman (Universitas Banda Naira, 2025)
This study examines the historical development of pok-pok, a traditional sea transportation, and its important role in shaping the social and economic life of the seafaring community in Boiyauw Village, Banda District, Central Maluku. Pok-pok has long been the main link between islands in the Banda Islands, helping daily activities while supporting the livelihoods of coastal communities. This study uses a historical method with a qualitative descriptive approach, collecting data through in-depth interviews, direct observations in the field, documentation and related literature reviews. Data are analyzed based on key themes to understand the historical, social, and economic roles of pok-pok in the region. The results of the study show that pok-pok is not just an ordinary means of transportation. Pok-pok plays an important role in maintaining the sustainability of the local economy, facilitating the mobility of workers, and strengthening social relations between communities on the surrounding islands. The use of pok-pok, which is still ongoing until now, proves the ability of local communities to survive and adapt to geographical challenges and the dynamics of economic change in the island environment.